Variational principles and methods in theoretical physics and chemistry - Nesbet, R. K. (Cambridge University Press, 2004)
A thorough introduction to variational theory as applied to physics and chemistry, introducing the fundamental mathematical concepts and applications, providing the reader with a critical understanding of context and methodology. Amongst other topics, the book covers current computational methods in quantum theory and discusses the methodology underlying density functional theory.